Changes in Hepatitis C Virus Genotype Distribution in Diyarbakır from 2011 to 2020: The Impact of Migration and Epidemiological Trends - Esra Yenihal; Selahattin Atmaca; Nida Özcan; Mahmut Mete (Journal of Global Antimicrobial Resistance)
OBJECTIVE: This study aims to investigate the Hepatitis C Virus (HCV) genotypes, changes in genotype distribution, and the effects of migration among chronic hepatitis C patients who presented at a university hospital in Diyarbakır over a decade. MATERIALS-METHODS: This cross-sectional retrospective study includes 815 patients who tested positive for HCV RNA at the Central Laboratory of Dicle University Hospital between January 2011 and December 2020. One sample per patient was included in the study. Genotype determination was performed on serum samples with detected HCV RNA using sequencing of the HCV genome obtained after amplification. RESULTS: Genotype 1 was detected in 768 cases (94.2%), genotype 2 in 5 cases (0.6%), genotype 3 in 27 cases (3.3%), genotype 4 in 14 cases (1.7%), and genotype 5 in one case (0.12%). The sample with genotype 5 was found to belong to a patient from Syria. It was observed that the prevalence of genotype 1 decreased over the years, while the prevalence of genotype 4 increased. The prevalence of genotype 3 increased in 2019 and 2020 and was found to be higher in male patients (88.8%) than in female patients.The increase in genotype 4 rates over the years in our region, along with the detection of genotype 5, indicates that migration from Syria has altered the genotype distribution. Additionally, the rise in genotype 3, which is known to be more common among patients who use intravenous drugs, highlights the presence of different factors affecting genotype distribution.